Novel Alanyl-tRNA Synthetase 2 Pathogenic Variants in Leukodystrophies - Wang, Xingao; Wang, Qun; Tang, Hefei; Chen, Bin; Dong, Xiang; Niu, Songtao; Li, Shaowu; Shi, Yuzhi; Shan, Wei; Zhang, Zaiqiang (Frontiers in Neurology, 2019)
To determine the novel AARS2 mutation implicated in leukodystrophy, in this study, several families with an autosomal recessive inheritance pattern of leukodystrophy were analyzed by whole-exome sequencing. Variants were prioritized according to their rarity and those pathogenic variants in genes already known to be associated with leukodystrophy and confirmed by Sanger sequencing using standard protocols. We identified 5 rare AARS2 variants (c.452T>C chr6:44279256 p.M151T, c.1871G>A chr6:44272054 p. W624X, c.802A>G chr6:44278128 p.M268V, c.1703-1704del chr6:-44272430-44272431 p. Q568fs, c.179C>A chr6-44280882 p. P60H) with varying penetrance in 4 independent Chinese leukodystrophy families. These single nucleotide variants (SNVs), or deletion mutations, induced a frameshift, causing a missense mutation in AARS2. These findings suggested that all mutations might contribute to the development of leukodystrophy in the examined family members. Combined with previous findings, our data confirmed that the novel mutations are in leukodystrophy-related risk genes. We also summarized all the AARS2 mutations related to the onset of leukodystrophy in adults.